Anti-tissue adhesion film and its preparation method and application
Patent Information
- Application Number
- CN202310732495.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-06-20
AI Technical Summary
但是将ALG掺入PCL制备抗组织粘连薄膜尚未见报道
[0034]1、在材料选择方面,所使用的材料组分I可被人体吸收,无毒害作用;组分II、Ⅲ都是生物相容性的高分子材料,而且可生物降解,对环境也无污染。组分Ⅲ延展性好,力学性能也很突出,有很好的弹性变形能力。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of Janus membranes, in particular to a novel Janus membrane for biological tissue engineering, one side of which can be cell-adherent and the other side of which is highly hydrophilic and can prevent adhesion of tissues such as peritendinous tissues, and also to a preparation method and application thereof. Background Art
[0002] Postoperative tissue adhesion is one of the most common challenges in clinical practice. Tissue adhesion often causes severe pain, organ functional obstruction, and sometimes leads to difficult reoperations, which significantly increase medical costs. Recent research has focused on the use of barrier materials that can physically isolate the injury site from adjacent tissues or organs and thus prevent tissue adhesion formation. They are easy to operate in laparoscopic and open surgery, biocompatible, biodegradable, immunologically inert, and do not interfere with wound healing.
[0003] The basic requirements for an ideal barrier material are considered to be resident stability at the application (injury) site during the wound healing period (7-10 days), no need for sutures, easy handling during laparoscopic and open surgery, biocompatibility, biodegradability, immunological inertness, and non-interference with wound healing. Appropriate anti-adhesion of polymers to cells or tissues in the body is one of the basic requirements for maintaining health and protecting the body from trauma and foreign bodies (Lih, E., et al. Polymers for cell / tissue anti-adhesion. Progress in Polymer Science 44(2015):28-61.). Regulating the anti-adhesion properties of biomedical polymers to cells has been considered a key parameter for the development of polymer biomaterials for biomedical applications such as artificial blood vessels and cell encapsulation.
[0004] In order to meet these criteria, many polymers can be prepared into polymer tissue anti-adhesion barriers with different structures and functions, such as sheet types (such as PVA, PLA, ALG, HA), solution / hydrogel types (such as PEG, PVP, DX), powder types (HA / CMC, HA / crosslinked ALG) and controlled drug release types (Ibuprofen / PLLA-PEG, Ibuprofen / PLLA). Alginate is a natural polysaccharide with good biocompatibility, gel-forming ability, non-toxicity, and biodegradability. It can be easily processed into 3D scaffold materials, including hydrogels, microcapsules, microspheres, foams, sponges, and fibers. Polycaprolactone (PCL) is an aliphatic semi-crystalline polymer with good biocompatibility, biodegradability, drug permeability, mechanical properties (manifested in high initial strength and long-lasting mechanical properties) and thermal stability, and is widely used in various fields of tissue engineering. Wang et al. studied the addition of gelatin to polycaprolactone electrospinning to obtain films with anti-myocardial adhesion and found that the gelatin / polycaprolactone (GT / PCL, mass ratio 50:50) film exhibited excellent mechanical properties, good biocompatibility and effective anti-cell permeability, which can be used as a physical barrier to prevent postoperative cardiac adhesion and may be suitable for other biomedical applications such as wound healing, guided tissue or bone regeneration (XA Wang, L. Xiang, YX Peng, ZH Dai, YQ Hu, XT Pan, XL Zhou, H. Zhang, B. Feng, Gelatin / Polycaprolactone Electrospun Nanofibrous Membranes: The Effect of Compositionand Physicochemical Properties on Postoperative Cardiac Adhesion, Frontiersin Bioengineering and Biotechnology 9 (2021).). However, the incorporation of ALG into PCL to prepare anti-tissue adhesion films has not been reported. Summary of the invention
[0005] In order to solve the above technical problems, the first purpose of the present invention is to provide a non-fibrous film with anti-tissue adhesion, which has a Janus structure, one side of which can be adhered to by cells, and the other side is highly hydrophilic, which can prevent adhesion of tissues such as tendons, and the raw materials used have good biocompatibility and are biodegradable.
[0006] The second object of the present invention is to provide a method for preparing an anti-tissue adhesion non-fibrous film, which does not require solvents, is environmentally friendly and non-toxic, and can obtain a mechanically enhanced film.
[0007] The third object of the present invention is to provide an application of an anti-tissue adhesion non-fibrous film, which can be used in biological tissue engineering scaffolds to prevent tissue adhesion on one side and facilitate cell adhesion on the other side. It has good biocompatibility and is expected to be applied in biomedical fields such as tendon repair and guided tissue regeneration.
[0008] In order to achieve the above technical objectives, the present invention provides an anti-tissue adhesion non-fibrous film, which is a Janus structure with asymmetric two sides, one side is a film A with anti-tissue adhesion, including components I and II, and the other side is a film B with cell adhesion, including component III; the component I is an adhesion inhibitor; the component II is a polymer material with biocompatibility and absorbable in vivo; the component III is a polymer material with biocompatibility, absorbability, ductility and elastic deformation ability.
[0009] The anti-tissue adhesion film of the present invention is composed of two films with different properties. The film A with anti-tissue adhesion on one side includes component I and component II. Component I is an adhesion inhibitor with strong hydrophilicity and can achieve the effect of anti-tissue adhesion; component II is a carrier of component I, with stable chemical properties and no reaction with component I, and has good biocompatibility and fast degradation in the body, and can be implanted as a stent. The film B with cell adhesion on the other side includes component III, which has stable chemical properties, good biocompatibility and degradation performance, and also has good ductility, can be prepared into a cast film, and also has good elastic deformation ability. After the stretching process, it obtains good mechanical properties and can meet the requirements of high-intensity sports parts such as tendon and ligament repair.
[0010] As a preferred solution, the component I is at least one of alginate and its derivatives, agar and its derivatives, hydroxypropyl methylcellulose (HPMC) and its derivatives, methylcellulose (MC) and its derivatives, hydroxyethyl cellulose (HEC) and its derivatives, chitosan and its derivatives, polyvinyl alcohol and its derivatives. The preferred adhesion inhibitor has strong hydrophilicity, can inhibit cell adhesion, and has biocompatible and biodegradable properties.
[0011] As a preferred solution, the component II is at least one of polycaprolactone and its derivatives, polyhydroxybutyrate and its derivatives, polylactic acid and its derivatives. The preferred polymer material has good biocompatibility, is biodegradable, and the degradation products are only water and carbon dioxide, which is non-toxic and environmentally friendly.
[0012] As a preferred solution, the component III is at least one of polycaprolactone and its derivatives, polylactic acid and its derivatives. The preferred polymer material not only has biocompatibility and biodegradability, but also has good tensile strength and ductility, good thermal stability and is suitable for processing methods such as thermoplastics.
[0013] As a preferred solution, the mass ratio of component II to component I is 1:1-3:7; the mass ratio of the total mass of component I plus component II to component III is 1:1-1:2.
[0014] The present invention also provides a method for preparing an anti-adhesion Janus film, comprising the following steps:
[0015] 1) Component I is placed in a crusher for crushing, and the crushing step is repeated 2-3 times;
[0016] 2) Collect the crushed component I powder, sieve it through 100-150 mesh and 300-400 mesh stainless steel sieves, and collect the component I powder passing through the 300-400 mesh sieve into a clean centrifuge tube;
[0017] 3) Weigh the corresponding mass of component II and place it between the rollers of the open mill, allowing it to be evenly wrapped on the rollers. Then sprinkle the powder of component I evenly on component II, and the content of component I should be less than 80 wt.%; every 20-40 minutes, pause the rollers and increase the spacing, shovel the material to the middle of the rollers with a clean wooden shovel, and then adjust the roller spacing back to 0.3-0.6 mm for mixing, and repeat the above steps 2-3 times. When component II and component I are completely mixed, increase the roller spacing, take an appropriate amount of material with a wooden shovel, and press it into a cake;
[0018] 4) Repeat step 3) to make component III into a cake;
[0019] 5) Place the cake obtained in step 3) between stainless steel foils of the same size, and finally clamp it between stainless steel plates in a hydraulic flat vulcanizer. Adjust the parameters to apply pressure, and take out film A after natural cooling. The specific process parameters are: the temperature of the upper and lower plates is 80-120 ℃, the heating time is 15-30 min, and the pressure holding time is 30-60 min;
[0020] 6) The cake obtained in step 4) is sandwiched between stainless steel foils, and then clamped with stainless steel plates, and placed between the upper and lower steel plates of a hydraulic flat plate vulcanizer, so that the upper part of the stainless steel plate is in contact with the upper plate, heated and pressure maintained, and film B is taken out after natural cooling. The specific process parameters are: the temperature of the upper and lower plates is 80-120 °C, the heating time is 15-30 min, and the pressure maintenance time is 30-60 min;
[0021] 7) Place a stainless steel plate on the glue drying machine, heat the steel plate to 50-80℃ to make film B fit the steel plate, and then raise the temperature to 100-120℃ until film B melts;
[0022] 8) Covering the film A obtained in step 5) on the melted film B, stopping heating and allowing it to cool naturally; the heating temperature is 50°C-80°C;
[0023] 9) After the steel plate returns to room temperature, slowly peel off the Janus membrane from one corner of the steel plate and clean the burrs to obtain the Janus membrane.
[0024] As a preferred solution, in step 3), the mass ratio of component I to component II is 1:1-3:7. When the content of component I reaches 80 wt.%, the mixture on the roller of the mixing mill gradually becomes loose and loses viscosity with the addition of component I powder. The preferred mass ratio of ALG is 40%-75%.
[0025] As a preferred solution, in step 3), the process parameters for mixing component I and component II to form a cake are: preheating temperature of 80-120°C, roller spacing of 0.3-0.6 mm, and rotation speed of 1-2 rpm.
[0026] As a preferred solution, in step 4), the process parameters for preparing component III into a cake are: preheating temperature of 80-120°C, roller spacing of 0.3-0.6 mm, and rotation speed of 1-2 rpm.
[0027] The present invention also provides a method for preparing an anti-adhesion Janus film, wherein the prepared Janus film is stretched, kept warm for a period of time after the stretching, and then taken out to obtain an anti-tissue adhesion film, wherein the temperature of the stretching machine is 30-60°C and the temperature is kept warm for 30-60 min; the stretching process parameters are: a stretching multiple of 2-5 times, a deformation limit of 60-100 mm, a stretching speed of 3-6 mm / min, and a preloading speed of 3-6 mm / min.
[0028] As a preferred solution, in step 1), the long side of the Janus film is parallel to the length direction of the test paper, and 0.5-1 cm is left on both sides of the length direction of the test paper to prevent the Janus film from slipping from the clamp of the stretching machine during the hot stretching process.
[0029] As a preferred solution, the temperature of the stretching machine is 50°C and the temperature is kept for 30 min; the stretching process parameters are: stretching multiple is 3 times, deformation limit is 90 mm, stretching speed is 5 mm / min, and preloading speed is 5 mm / min.
[0030] The present invention also provides the use of the anti-tissue adhesion film or the anti-tissue adhesion film prepared by any one of the above methods in preparing tendon repair and guided tissue regeneration materials.
[0031] The present invention provides a Janus film with anti-tissue adhesion and a preparation method thereof: first, component I with anti-adhesion performance is added to polymer material component II, and the mixture is uniformly mixed in an open mill to form a cake. Then, a flat vulcanizer is used to press the film A; the polymer material component III is subjected to the same steps to form a film B. Finally, film A is compounded onto film B on a glue drying machine to obtain a Janus film. Among them, component I has strong hydrophilicity and can achieve the purpose of anti-tissue adhesion; component II mainly provides a bonding effect for component I, so that it can be leveled into a film, and at the same time provides a certain mechanical strength; component III has good thermal processing performance and thermal stability, can be hot-pressed into a film, and has good elastic deformation ability, so that the Janus film has good mechanical properties as a tissue engineering scaffold.
[0032] The present invention uses the Janus film with anti-tissue adhesion to prepare the tissue engineering scaffold with anti-tissue adhesion through the stretching process: first, the biocompatibility of the Janus film is given by components I, II, and III, component I is highly hydrophilic and absorbable, component II and component III are both biocompatible medical materials, and are biodegradable, and the degradation products are non-toxic and environmentally friendly, and do not pollute the environment; second, the anti-tissue adhesion effect of the Janus film inhibits cell adhesion through the strong hydrophilicity of component I, thereby achieving the cutting off of the adhesion formation process in the early stage of inflammation; third, the good mechanical properties of the Janus film are obtained through component III, and the excellent rheological and viscoelastic properties of component III make it easy to manufacture and operate into a tissue scaffold, and it has good mechanical strength. Fourth, the anti-adhesion tissue engineering scaffold is obtained by the Janus film through the stretching process, and the film B side formed by the film of component III is more suitable for cell attachment after stretching, which can achieve the purpose of promoting cell adhesion, and the film A side formed by the film of component I and component II is more hydrophilic after stretching, which will make it more difficult for cells to attach, so it can better achieve the purpose of anti-tissue adhesion.
[0033] Compared with the existing films for anti-tissue adhesion, the technical solution of the present invention has the following advantages:
[0034] 1. In terms of material selection, the material component I used can be absorbed by the human body and has no toxic effects; components II and III are both biocompatible polymer materials, and are biodegradable and environmentally friendly. Component III has good ductility, outstanding mechanical properties, and good elastic deformation ability.
[0035] 2. In terms of preparation technology, the film preparation technology of hot pressing molding is adopted. No solvent is added in the process, which avoids the problem of solvent volatilization polluting the environment and harming the operator. In addition, through the stretching process, the film is strain-strengthened and the mechanical properties are improved.
[0036] 3. The anti-tissue adhesion scaffold made by the stretching process makes the properties of the two sides of the Janus membrane more asymmetric. One side is more suitable for cell attachment after stretching, which can promote cell adhesion; the other side is more hydrophilic after stretching, making it more difficult for cells to attach, which can better achieve the purpose of anti-tissue adhesion. In addition, the long-term degradation of component III enables it to provide mechanical support for the damaged area as an implant, providing a place and a long-term stable microenvironment for tissue regeneration and repair.
[0037] In summary, the present invention proposes to prepare an anti-tissue adhesion tissue engineering scaffold through a stretching process based on natural antioxidants and medical polymer materials. Not only is the material biocompatible and absorbable, but it also has Janus properties. Through the stretching process, the scaffold is mechanically enhanced, and the effect of hydrophilic anti-tissue adhesion on one side and promoting cell adhesion on the other side is achieved. The detailed structure of the present invention is further described below in conjunction with the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The macroscopic morphology of the Janus membrane in Comparative Example 1: (a) Janus membrane-PCL side; (b) Janus membrane-ALG / PCL side.
[0039] Figure 2 SEM images of the Janus membrane in Comparative Example 1: (a) × 200 PCL side; (b) × 2000 PCL side; (c) × 200 ALG / PCL side; (d) × 2000 ALG / PCL side.
[0040] Figure 3 This is the double-sided water contact angle-time curve of the Janus film in Comparative Example 1 (n=5).
[0041] Figure 4 The stress-strain curves of different membranes in Comparative Example 1 (n=3): (a) PCL membrane; (b) ALG / PCL (70%) membrane; (c) Janus membrane. The right side of the figure is a partial enlarged view of the elastic deformation area in the complete tensile curve on the left.
[0042] Figure 5 is a photo of the PCL / ALG film morphology in Example 1: (a) 4×4cm² 0% ALG (pure PCL); (b) 4×4cm² 70% ALG; (c) 1×1cm² 0% ALG (PCL); (d) 1×1cm² 30% ALG; (e) 1×1cm² 50% ALG; (f) 1×1cm² 70% ALG.
[0043] Figure 6 This is a photograph of the 80 wt. % ALG mixing process in Example 1 (the white arrow in the figure indicates the mixed copolymer that fell off the roller and broke during the mixing process).
[0044] Figure 7 The water contact angle-time variation curves of PCL / ALG films with different ALG contents in Example 1 (n=5).
[0045] Figure 8 The SEM images (×1000) of the corresponding surfaces of the samples at different composite heating temperatures in Example 2 are as follows: (a) 60℃ PCL side; (b) 60℃ ALG side; (c) 70℃ PCL side; (d) 70℃ ALG side; (e) 80℃ PCL side; (f) 80℃ ALG side; (g) 90℃ PCL side; (h) 90℃ ALG side; (i) 100℃ PCL side; (j) 100℃ ALG side.
[0046] Fig. 9 The water contact angle-time variation curves of the two surfaces of the film at different composite heating temperatures in Example 2 (n=5): (a) 60℃ Janus film; (b) 70℃ Janus film; (c) 80℃ Janus film; (d) 90℃ Janus film; (e) 100℃ Janus film.
[0047] Fig.10 The macroscopic morphology of the s-Janus membrane after stretching in Example 3: (a) s-Janus membrane-PCL side; (b) s-Janus membrane-ALG / PCL side.
[0048] Fig.11 SEM images of the s-Janus membrane after stretching in Example 3: (a) × 200 PCL side; (b) × 2000 PCL side; (c) × 200 ALG / PCL side; (d) × 2000 ALG / PCL side.
[0049] Fig.12The water contact angles on both sides of the Janus membrane before and after stretching treatment in Example 3 vary with time: (a) Janus membrane; (b) s-Janus membrane.
[0050] Fig.13 The complete and locally enlarged stress-strain curves of different membranes in Example 3: (a) PCL membrane; (b) ALG / PCL membrane; (c) Janus membrane; (d) s-Janus membrane.
[0051] Fig.14 These are photos of the Janus film degradation at 1d, 3d, 7d, 30d, and 42d before and after stretching in Example 3.
[0052] Fig.15 3 is a curve showing the weight loss rate of the Janus film before and after stretching versus time. DETAILED DESCRIPTION
[0053] The following specific examples are intended to further illustrate the present invention rather than to limit the scope of protection of the claims.
[0054] Unless otherwise specified, the chemical reagents involved in the following examples are all conventional commercially available reagents. The molecular weight of the polycaprolactone in the following comparative examples and examples is Mn=80,000.
[0055] Comparative Example 1
[0056] This comparative example illustrates the Janus characteristics
[0057] Step 1: Raw material preparation
[0058] Weigh 150 g of ALG particles and put them into the crusher for crushing. The crusher works for 1 min, rests for 20 min, and repeats the above crushing steps three times. Let it stand for 10 min, and sieve the crushed ALG powder using 150 mesh and 300 mesh stainless steel sieves successively. Collect the ALG powder that has passed the 300 mesh sieve into a clean centrifuge tube for later use.
[0059] Step 2: PCL Cake Preparation
[0060] Weigh 40 g of PCL particles, preheat the mill to 90 °C, set the roller spacing to 0.4 mm, and set the speed to 1 rpm. Place the PCL particles between the rollers and let them wrap evenly on the rollers. Pause the rollers and increase their spacing every 20 minutes, shovel the material to the middle of the rollers with a clean wooden shovel, and then adjust the roller spacing back to 0.4 mm to mix. Repeat the above steps three times. After mixing, use a wooden shovel to take about 5 g of material at a time and press it into a cake.
[0061] Step 3: ALG / PCL Cake Preparation
[0062] Weigh 18 g of PCL particles and 42 g of ALG particles through a 300-mesh sieve, i.e., ALG accounts for 70% of the total mass. Preheat the open mill to 120 °C, set the roller spacing to 0.4 mm, and set the speed to 1 rpm. First, place the PCL particles between the rollers and let them wrap evenly on the rollers. Every 20 minutes, pause the rollers and increase the spacing. Use a clean wooden shovel to shovel the material to the middle of the rollers, then adjust the roller spacing back to 0.4 mm for mixing. Repeat the above steps three times. When ALG and PCL are completely mixed, increase the roller spacing, use a wooden shovel to take about 7 g of material at a time, and press it into a cake.
[0063] Step 4: Preparation of PCL membrane
[0064] The material cake is sandwiched between stainless steel foils, and then clamped with stainless steel plates, and placed between the upper and lower steel plates of the hydraulic flat plate vulcanizer. After starting the lamination, the upper plate preheating temperature is set to 90 ℃, the lower plate preheating temperature is set to 90 ℃, and the upper and lower plates are heated at the same time. After 15 minutes, the heating is completed, the holding time is set to 1 hour, and the PCL film can be taken out after natural cooling for about 8 hours.
[0065] Step 5: Preparation of ALG / PCL membrane
[0066] Place the prepared cake on two pieces of 25 × 25 cm 2 PET, and then sandwiched between 25 × 25 cm 2 The film was sandwiched between 304 stainless steel foils and then between 304 stainless steel plates in the hydraulic flat plate vulcanizer. The lower plate was manually raised so that the 304 stainless steel plate just touched the upper plate. The parameters were adjusted so that the temperature of the upper and lower plates was 110°C and heated at the same time. After 20 minutes of heating, pressure was applied and the holding time was set to 30 minutes. After cooling naturally for 12 hours, the ALG / PCL film was removed.
[0067] Step 6: Composite of PCL and ALG / PCL film
[0068] The prepared ALG / PCL membrane was removed from the PET and cut into 3 × 6 cm 2The PCL membrane was cut into a smaller rectangle of 4 × 7 cm2. A round 304 stainless steel plate was placed on the glue drying machine and heated to 60 °C. The PCL membrane was bonded to the steel plate with flat-tipped tweezers. The temperature was then adjusted to 110 °C and kept for 5 min to completely melt. The ALG / PCL membrane was then covered on the melted PCL and the heating was stopped to allow it to cool. After returning to room temperature, the Janus membrane was removed and the excess PCL was cleaned off to obtain a 3 × 6 cm 2 Size of Janus membrane.
[0069] In this comparative example, Figure 1 As shown in the figure, the PCL side surface is smooth and reflective, while the ALG / PCL side surface is rough and matte. The surface microstructure of the composite Janus membrane was characterized, as shown in the figure. Figure 2 As shown in the figure, when observed at 200 times, the surface of the PCL side is relatively flat and has no obvious defects. When observed at 2000 times, there are no protrusions caused by ALG particles on the surface, that is, during the composite process, ALG did not diffuse to the PCL side, which means that the composite process of PCL and ALG / PCL film is feasible. The surface of the ALG / PCL side is a protrusion caused by ALG particles, and it was observed that there was no obvious agglomeration phenomenon, indicating that the ALG particles are evenly distributed in PCL.
[0070] In this comparative example, the water contact angle test results ( Figure 3 ) showed that during the test time of 0-9 minutes, the water contact angle on the PCL side of the same film changed from 72.787° to 48.106°, while the water contact angle on the ALG side changed from 66.411° to 29.289°. The above test results prove that the two surfaces of the Janus film have asymmetric hydrophilicity and hydrophobicity.
[0071] In this comparative example, the three different membranes showed great differences in specific mechanical properties ( Figure 4), the Young's modulus, yield stress (strain), and fracture stress (strain) of the PCL / ALG membrane are all worse than those of the PCL membrane. However, compared with the PCL / ALG membrane, the five mechanical properties of the Janus membrane have shown significant improvements, among which the Young's modulus and yield strength have increased by 33.5% and 56%, respectively, which means that the tendon scaffold shell prepared by the Janus membrane can withstand a greater degree of tensile stress while maintaining the stability of the damaged area; and the yield strain has increased by 143%, reaching 5.57%, which is very close to the average peak strain of human tendons of 6~8%, and is higher than the elongation of daily exercise by 4%; the fracture strength and fracture strain have increased by 122% and 4881%, respectively. The above results not only prove that the bonding between the two layers of the membrane is very good under the double-layer composite process, but also prove that the Janus membrane has good mechanical properties and is expected to be used in tendon shell scaffolds. Example 1
[0072] Step 1: Raw material preparation
[0073] Weigh 200 g of ALG particles and put them into a crusher for crushing and refining. Repeat the operation three times, then take out the crushed ALG powder and sieve it with 150-mesh and 400-mesh stainless steel sieves respectively. Put the 400-mesh sieved material in a centrifuge tube for later use.
[0074] Step 2: Preparation of PCL / ALG composite cake
[0075] First, according to different blending ratios, ALG wt.% was 0%, 30%, 50%, 70%, and 80%, respectively. 30g, 21g, 20g, 18g, and 18g of PCL particles and 0g, 9g, 20g, 42g, and 72g of ALG powder obtained in the first step were weighed for use. Start the double-shaft open rubber mixer, set the heating temperature to 100℃, adjust the roller rotation rate to 1-2 rpm, and the distance between the two rollers is 4 mm. Put the PCL particles into the open mixer, wait for them to be completely melted, add ALG powder that has passed through a 150-mesh sieve and blend. Concentrate the materials to the middle of the roller every 30 minutes and extrude and mix again. After repeating more than 3 times, collect the PCL / ALG composite material and press it into a cake.
[0076] Step 3: Preparation of PCL / ALG composite film
[0077] Take the cake and place it in the middle of two PET plates, then clamp stainless steel foil and steel plate on both sides and put it into the hydraulic flat plate vulcanizer. Set the upper and lower plates to 110℃, and automatically maintain the pressure for 1 hour after heating and pressurizing. After the pressure is maintained, cool it with the furnace for 12 hours to room temperature and then take out the film.
[0078] In this embodiment, different blending ratios, i.e., ALG wt.% of 0%, 30%, 50%, and 70%, respectively, can be mixed to form films ( Figure 5 ), after the ALG content reached 80 wt.%, the mixture on the roll of the mixing mill gradually became loose and lost its viscosity. The polymer mixture that originally tightly wrapped the roll began to fall off and could not be re-fused, and the newly added ALG powder could not be dispersed ( Figure 6 ).
[0079] In this embodiment, the water contact angle test results of different blending ratios are compared and it is found that Figure 7 As shown in the figure, with the increase of ALG content, the difference between the experimental group (ALG wt.% is 30%, 50%, 70%) and the control group (ALG wt.% is 0%) increases, and the degree of decrease of the water contact angle over time increases, which proves that the incorporation of ALG can enhance the hydrophilicity of the material, and this enhancement effect increases with the increase of ALG content. The preferred mass ratio of ALG wt.% is 50%-70%. Example 2
[0080] Step 1: Raw material preparation
[0081] Weigh 200 g of ALG particles and put them into a crusher for crushing. Let it stand for 15 minutes, and sieve the crushed ALG powder through 100-mesh and 300-mesh stainless steel sieves successively. Collect the ALG powder that has passed the 300-mesh sieve into a clean centrifuge tube for later use.
[0082] Step 2: PCL Cake Preparation
[0083] Weigh 40 g of PCL particles, preheat the mill to 90 °C, set the roller spacing to 0.5 mm, and set the speed to 1.5 rpm. Place the PCL particles between the rollers and evenly wrap them around the rollers. Pause the rollers and increase the spacing every 15 minutes, shovel the material to the middle of the rollers with a clean wooden shovel, and then adjust the roller spacing back to 0.5 mm for mixing. Repeat the above steps three times. After mixing, take about 5 g of the material and press it into a cake.
[0084] Step 3: ALG / PCL Cake Preparation
[0085] Weigh 18 g of PCL particles and 42 g of ALG powder that has passed a 300-mesh sieve, i.e., ALG accounts for 70% of the total mass. Preheat the mill to 110 °C, set the roller spacing to 0.3 mm, and set the speed to 1 rpm. First, place the PCL particles between the rollers and allow them to be evenly wrapped on the rollers. Every 20 minutes, pause the rollers and increase the spacing. Use a clean wooden shovel to shovel the material to the middle of the rollers, then adjust the roller spacing back to 0.3 mm for mixing. Repeat the above steps three times. When ALG and PCL are completely mixed, increase the roller spacing, take about 7 g of the material, and press it into a cake.
[0086] Step 4: Preparation of PCL membrane
[0087] The material cake is sandwiched between stainless steel foils, and then clamped with stainless steel plates, and placed between the upper and lower steel plates of the hydraulic flat plate vulcanizer. After starting the lamination, the upper plate preheating temperature is set to 100 ℃, the lower plate preheating temperature is set to 100 ℃, and the upper and lower plates are heated at the same time. After 20 minutes of heating, the holding time is set to 1 hour. After natural cooling for about 8 hours, the PCL film can be taken out.
[0088] Step 5: Preparation of ALG / PCL membrane
[0089] Place the prepared cake between PET, then between stainless steel foil, and finally between 304 stainless steel plates in a hydraulic flat plate vulcanizer. Manually raise the lower plate so that the stainless steel plate just touches the upper plate. Adjust the parameters so that the temperature of the upper and lower plates is 120 °C and heat at the same time. After 20 minutes of heating, apply pressure and set the holding time to 30 minutes. Cool naturally for 12 hours and then remove the ALG / PCL film.
[0090] Step 6: Composite of PCL and ALG / PCL film
[0091] Pure PCL membrane and PCL / ALG (70 wt.% ALG) membrane were double-layered at 60°C, 70°C, 80°C, 90°C, and 100°C, respectively, with a holding time of 2 min. After cooling to room temperature, the Janus membrane was removed and the excess PCL was cleaned to obtain a 3 × 6 cm 2 Size of Janus membrane.
[0092] In this implementation, Figure 8 As can be seen from (ad), the asymmetry of the two sides of the film at 60℃ and 70℃ is very obvious. Figure 8(e, f) show that when the temperature reaches 80℃, the morphological difference between the two sides is reduced to the minimum, and the original particles and grooves are almost non-existent on the ALG side. When the heating temperature is increased to 90℃ and 100℃, Figure 8 (gj) It can be seen that the fusion degree of the two layers of the membrane is further strengthened, and ALG particles begin to appear on the PCL side. The results show that the asymmetry of the Janus membrane gradually weakens with the increase of temperature. The preferred heating temperature is 60℃-70℃.
[0093] In this embodiment, from Fig. 9 It can be seen from all sub-figures that the experimental samples of all temperature parameters show differences in hydrophilicity / hydrophobicity on both sides of the film, which further proves functionally that a Janus membrane with asymmetric surface properties has been constructed. Example 3
[0094] Step 1: Raw material preparation
[0095] Weigh 150 g of ALG particles and put them into a crusher for crushing. Repeat the above crushing steps three times. Let it stand for 20 minutes, and sieve the crushed ALG powder through 150 mesh and 350 mesh stainless steel sieves successively. Collect the ALG powder that has passed the 350 mesh sieve into a clean centrifuge tube for later use.
[0096] Step 2: PCL Cake Preparation
[0097] Weigh 50g of PCL particles, preheat the mill to 90℃, set the roller spacing to 0.4mm, and set the speed to 1rpm. Place the PCL particles between the rollers and evenly wrap them on the rollers. Pause the rollers and increase the spacing every 20 minutes, shovel the material to the middle of the rollers with a clean wooden shovel, and then adjust the roller spacing back to 0.4mm for mixing. Repeat the above steps three times. After mixing, take about 6g of the material and press it into a cake.
[0098] Step 3: ALG / PCL Cake Preparation
[0099] Weigh 21 g of PCL particles and 49 g of ALG powder that has passed a 350-mesh sieve, i.e., ALG accounts for 70% of the total mass. Preheat the mill to 120 °C, set the roller spacing to 0.4 mm, and set the speed to 1 rpm. First, place the PCL particles between the rollers and allow them to be evenly wrapped on the rollers. Every 20 minutes, pause the rollers and increase the spacing. Use a clean wooden shovel to shovel the material to the middle of the rollers, then adjust the roller spacing back to 0.4 mm for mixing. Repeat the above steps three times. When ALG and PCL are completely mixed, increase the roller spacing, take about 8 g of the material, and press it into a cake.
[0100] Step 4: Preparation of PCL membrane
[0101] The material cake is sandwiched between stainless steel foils, and then clamped with stainless steel plates, and placed between the upper and lower steel plates of the hydraulic flat plate vulcanizer. After starting the lamination, the upper plate preheating temperature is set to 100 °C, the lower plate preheating temperature is set to 90 °C, and the upper and lower plates are heated at the same time. After 20 minutes of heating, the holding time is set to 1 hour, and the PCL film can be taken out after natural cooling for about 8 hours.
[0102] Step 5: Preparation of ALG / PCL membrane
[0103] Place the prepared cake between PET, then between 304 stainless steel foil, and finally between 304 stainless steel plates in the hydraulic flat plate vulcanizer. Manually raise the lower plate so that the stainless steel plate just touches the upper plate. Adjust the parameters so that the temperature of the upper and lower plates is 120 ℃, and heat at the same time. After 20 minutes of heating, apply pressure and set the holding time to 30 minutes. Cool naturally for 12 hours and then remove the ALG / PCL film.
[0104] Step 6: Composite of PCL and ALG / PCL film
[0105] The prepared ALG / PCL membrane was removed from the PET and cut into 3 × 6 cm 2 The PCL membrane was cut into smaller rectangles of 4 × 7 cm 2 Place a round 304 stainless steel plate on the glue drying machine, heat it to 50 °C, use flat-tipped tweezers to fit the PCL film to the steel plate, then adjust the temperature to 110 °C and keep it for 5 minutes to completely melt it. Then cover the melted PCL with the ALG / PCL film, then stop heating and let it cool. After returning to room temperature, remove the Janus film and clean off the excess PCL to obtain a 3 × 6 cm2 Size of Janus membrane.
[0106] Step 7: Drawing of Janus membrane
[0107] The prepared Janus membrane was cut into 1.5 × 6 cm pieces using a scalpel. 2 A long rectangle of 4 × 5 cm 2 Cut a 3 × 3 cm square in the middle of the test paper. 2 The size of the hollow square, that is, the original length of the stretching area is 3 cm. Use label paper to tightly fit the Janus membrane and the test paper and fix them on the fixture. Use the remote control to make fine adjustments so that the Janus membrane is just taut, cut the papers on both sides with a scalpel, and close the door of the stretching machine. Turn on the heating switch of the stretching machine, heat to 55 ℃, and keep warm for 30 minutes. The stretching multiple is 4 times, that is, the deformation limit is 120 mm, the stretching speed is 5 mm / min, and the preloading speed is also 5 mm / min. After the stretching is completed, keep it for 20 minutes, turn off the heating switch, and take out the s-Janus membrane obtained after stretching. The s-Janus membrane is a biological tissue engineering scaffold.
[0108] In this embodiment, the Janus film is stretched in a high temperature mechanical stretching machine, and the macroscopic morphology of the obtained s-Janus film is as follows: Fig.10 As shown in Figure 11. The PCL side has obvious stretching marks and a smooth surface; while the ALG / PCL side changes from yellow to off-white. During the stretching process, part of the ALG particles are buried in the PCL, and the ALG and PCL are more tightly combined. The rest are exposed on the surface, making the surface rough. The surface micromorphology of the s-Janus membrane obtained after stretching was characterized, as shown in Figure 11. At 200 times, the PCL side of the s-Janus membrane showed obvious ups and downs, and at 2000 times, many ridge / groove structures were formed on the surface of the PCL side. These structures are evenly distributed and can provide attachment points for cells, making it possible to promote cell adhesion. At 2000 times, unlike the ALG particles on the ALG / PCL side of the Janus membrane, which are all exposed, some ALG particles are exposed on the ALG / PCL side of the s-Janus membrane, and some ALG particles are encapsulated in PCL, which may reduce its degradation rate.
[0109] In this embodiment, the change of water contact angle on both sides of the unstretched Janus film over time ( Fig.12 ): The water contact angle on the PCL side changed from 71.10° to 45.12°, and the ALG / PCL side changed from 69.08° to 26.63°; the change of water contact angle on both sides of the s-Janus membrane with time after stretching: the PCL side changed from 84.14° to 57.65°, and the ALG / PCL side changed from 76.28° to 20.88°. The results show that the difference in water contact angles on both sides is more obvious, more in line with the definition of Janus membrane, and more asymmetric in nature. Secondly, the optimal water contact angle for cell attachment is about 60°, which means that the PCL side is more suitable for cell attachment after stretching, and can achieve the purpose of promoting cell adhesion; the water contact angle on the ALG / PCL side can reach 20° after stretching, which means that the hydrophilicity is stronger than that without stretching, which will make it more difficult for cells to attach, so it can better achieve the purpose of anti-tissue adhesion.
[0110] In this embodiment, the stress-strain curves of the precursor film and the Janus film before and after stretching are analyzed ( Fig.13 ) found that after the addition of ALG particles, the ability to resist stretching and deformation decreased sharply. From the complete stress-strain curve of ALG / PCL, it broke almost without any deformation. Compared with ALG / PCL, the Janus membrane after ALG / PCL and PCL film composite has increased deformation degree and stress, but it can still be clearly seen from the locally enlarged part that it has almost no elastic deformation stage and directly enters the plastic deformation area. It has no ability to resist recovery after stretching, and its deformation is very small and the stress it bears is also very small. Looking at the s-Janus membrane, whether from the complete image or from the locally enlarged image, the elastic deformation area can be clearly seen, and the slope is very large, which means that it has a relatively large Young's modulus. By comparison, it is found that the mechanical properties of the s-Janus membrane are much enhanced. This is because after the stretching treatment, the s-Janus membrane is in the strain strengthening stage, can withstand a relatively large tensile force and can recover to its original state, similar to the biomechanical properties of natural tendons, and is expected to be used as a scaffold material for tendon tissue engineering to repair damaged tendons.
[0111] In this embodiment, from Fig.14It can be seen intuitively that a lot of debris appeared on the first day of Janus membrane degradation, which was caused by the hydrolysis of ALG. As time went on, it slowly changed from yellow at the beginning to white, and finally completely dissolved in NaOH. Analysis shows that the ALG / PCL side is obviously degraded. The dissolution of ALG in the s-Janus membrane is a relatively slow process. At 30 days, signs of stratification were observed in the s-Janus membrane, indicating that the bonding force between the two layers of the membrane had subsided. At 42 days, the two layers of the membrane were completely separated, and the PCL side could still maintain its shape, but the ALG / PCL side had a higher content of ALG that was hydrolyzed, so the remaining PCL could not be formed and became flocs. Analysis of the weight loss rate of the Janus membrane before and after stretching as a function of time ( Fig.15 ), the weight loss rate of the unstretched Janus membrane reached 65.23% on the first day, which also shows that ALG has almost completely dissolved, while the weight loss rate of the stretched s-Janus membrane on the first day was 46.64%, and ALG was not completely dissolved and was slowly released over time. In the s-Janus membrane, some ALG particles were coated with PCL, and the degradation rate was reduced, which can well achieve the purpose of repairing damaged tendons.
[0112] The above is a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes according to the technical solutions and concepts of the present invention, which should be covered by the protection scope of the claims of the present invention.
Claims
1. An anti-tissue adhesion non-fibrous film, characterized in that: The anti-tissue adhesion non-fibrous film is a Janus structure with non-fibrous and asymmetric sides, one side is a film A with anti-tissue adhesion, including components I and II, and the other side is a film B with cell adhesion, including component III; the component I is an adhesion inhibitor; the component II is a polymer material with biocompatibility and absorbability in the body; the component III is a polymer material with biocompatibility, absorbability, ductility and elastic deformation ability; The mass ratio of component II to component I is 1:1-3:7; the mass ratio of the total mass of component I plus component II to component III is 1:1-1:2; The component I is at least one of alginate and its derivatives, agar and its derivatives, hydroxypropyl methylcellulose and its derivatives, methyl cellulose and its derivatives, hydroxyethyl cellulose and its derivatives, chitosan and its derivatives, polyvinyl alcohol and its derivatives; The component II is at least one of polycaprolactone and its derivatives, polyhydroxybutyrate and its derivatives, polylactic acid and its derivatives; The component III is at least one of polycaprolactone and its derivatives, polylactic acid and its derivatives; The anti-tissue adhesion non-fibrous film is obtained by the following preparation method: first, component I is added to component II, and the mixture is uniformly mixed in an open mill to form a cake, and then the cake is pressed into film A using a flat vulcanizer; the polymer material component III is subjected to the same steps to form film B, and finally film A is compounded onto film B on a glue drying machine to obtain a Janus film; the Janus film is stretched, and after the stretching is completed, the film is taken out after being kept warm for a period of time to obtain the anti-tissue adhesion film, and the stretching temperature is raised to 50-60° C. and kept warm for 30-60 min; the stretching process parameters are: a stretching multiple of 2-5 times, a deformation limit of 60-100 mm, a stretching speed of 3-6 mm / min, and a preloading speed of 3-6 mm / min.
2. The anti-tissue adhesion non-fibrous film according to claim 1, characterized in that: The component I is sodium alginate, the component II is polycaprolactone, and the component III is polycaprolactone.
3. The anti-tissue adhesion film according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: 1) Component I is placed in a crusher for crushing, and the crushing step is repeated 2-3 times; 2) Collect the crushed component I powder, sieve it through 100-150 mesh and 300-400 mesh stainless steel sieves, and collect the component I powder passing through the 300-400 mesh sieve into a clean centrifuge tube; 3) Weigh the corresponding mass of component II and place it between the rollers of the mixing mill, allowing it to be evenly wrapped on the rollers. Then sprinkle the powder of component I evenly on component II, and the content of component I is less than 80 wt.%; every 20-40 minutes, pause the rollers and increase the spacing, shovel the material to the middle of the rollers with a clean wooden shovel, and then adjust the roller spacing back to 0.3-0.6 mm for mixing, and repeat the above steps 2-3 times; when component II and component I are completely mixed, increase the roller spacing, take an appropriate amount of material with a wooden shovel, and press it into a cake; 4) Repeat step 3) to make component III into a cake; 5) Place the cake obtained in step 3) between stainless steel foils of the same size, and finally clamp it between stainless steel plates in a hydraulic flat vulcanizer; adjust the parameters to apply pressure, and take out the film A after natural cooling. The specific process parameters are: the temperature of the upper and lower plates is 80-120 °C, the heating time is 15-30 min, and the pressure holding time is 30-60 min; 6) The cake obtained in step 4) is sandwiched between stainless steel foils, and then clamped with stainless steel plates, and placed between the upper and lower steel plates of a hydraulic flat plate vulcanizer, so that the upper part of the stainless steel plate is in contact with the upper plate, heated and pressure maintained, and film B is taken out after natural cooling. The specific process parameters are: the temperature of the upper and lower plates is 80-120 °C, the heating time is 15-30 min, and the pressure maintenance time is 30-60 min; 7) Place a stainless steel plate on the glue drying machine, heat the steel plate to 50-80℃ to make film B fit the steel plate, and then raise the temperature to 100-120℃ until film B melts; 8) Covering the film A obtained in step 5) on the melted film B, stopping heating and allowing it to cool naturally; the heating temperature is 50°C-80°C; 9) After the steel plate returns to room temperature, slowly peel off the Janus membrane from one corner of the steel plate and clean the burrs to obtain the Janus membrane.
4. The anti-tissue adhesion film according to claim 1 or 2, characterized in that: The mass proportion of component I is 40%-75%.
5. The anti-tissue adhesion film according to claim 3, characterized in that: In step 3), the process parameters for mixing component I and component II to form a cake are: preheating temperature of 80-120 ° C, roller spacing of 0.3-0.6 mm, and rotation speed of 1-2 rpm; further, in step 4), the process parameters for making component III into a cake are: preheating temperature of 80-120 ° C, roller spacing of 0.3-0.6 mm, and rotation speed of 1-2 rpm.
6. The anti-tissue adhesion film according to claim 1 or 2, characterized in that: The stretching temperature is raised to 50°C and kept warm for 30 minutes; the stretching process parameters are: stretching multiple is 3 times, deformation limit is 90 mm, stretching speed is 5 mm / min, and preloading speed is 5 mm / min.
7. Use of the anti-tissue adhesion film according to any one of claims 1 to 6 in the preparation of tendon repair and guided tissue regeneration materials.
Citation Information
Patent Citations
Degradable compound biomaterial membrane for medical purpose
CN1994476A